NEGATIVE AND POSITIVE CHANGES IN ADOLESCENT BEHAVIOR (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
In this article, the peculiarities of studying the manifestation of behavioral deviations in adolescents and some general aspects related to behavioral deviations in adolescence are studied from the point of view of social psychology, the interaction of adolescents in the development of society. and the scientific studies that can show the necessity of the problem of their behavior in conflict situations and justify its "methodological roots" are highlighted.